2018
DOI: 10.31901/24566322.2018/22.1-3.1061
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Novice Primary School Head Teachers in Botswana

Abstract: This paper examines best basic leadership styles that can be used by principals to improve academic performance of learners in rural schools. Authors argue that basic leadership styles can have positive effects in learner performance. The study was conducted in best performing rural schools in the Eastern Cape Province. The belief is that poor performing schools can learn from successful schools. A phenomenological study with an interpretive-constructivism approach was conducted to establish basic leadership s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Despite the expectation that schools leaders as change agents would effectively implement the PMS in junior secondary schools, monitor teachers performance closely, improve school results, all it appears unachievable. Several studies conducted on PMS implementation in the education sector revealed that PMS has been inadequately and unsatisfactorily implemented in junior secondary schools, that there is poor measuring of teacher's performance, and a continuous decline of junior secondary schools examination results in Botswana (Koruyezu, 2010;Bulawa, 2011;Nkwe, 2015;Molefhi, 2015, Pheko, Bathuleng & Kgosidialwa, 2018.…”
Section: Developing a Perspective On School Leaders As Change Agents ...mentioning
confidence: 99%
“…Despite the expectation that schools leaders as change agents would effectively implement the PMS in junior secondary schools, monitor teachers performance closely, improve school results, all it appears unachievable. Several studies conducted on PMS implementation in the education sector revealed that PMS has been inadequately and unsatisfactorily implemented in junior secondary schools, that there is poor measuring of teacher's performance, and a continuous decline of junior secondary schools examination results in Botswana (Koruyezu, 2010;Bulawa, 2011;Nkwe, 2015;Molefhi, 2015, Pheko, Bathuleng & Kgosidialwa, 2018.…”
Section: Developing a Perspective On School Leaders As Change Agents ...mentioning
confidence: 99%